Revitalizing Classical Arabic Literature as a Basis for Character Education: A Literary Analysis of Imad al-Isfahani’s Poetry - Muhammad Hagdhak Al-Ghafiqi (Journal of Educational Research and Learning Analytics, 2026)
This research addresses moral degradation in Indonesia's 2025 educational landscape by revitalizing classical Arabic literature. It specifically analyzes Imad al-Isfahani’s poem "Jika Kau Tahu Akhir Dukanya" using Ahmad al-Shaib’s theory of literary elements: idea, emotion, imagination, and image. Employing a qualitative library research method, the study explores how these elements reconstruct the panegyric genre (madih) for Shihab al-Din al-Muzaffar. Findings reveal that the poem portrays an archetype of the "suffering leader," emphasizing sacrifice, resilience, and spiritual integrity. These values align with the Profil Pelajar Pancasila, offering a substantive alternative to purely grammatical approaches in Arabic language teaching. By transforming literature into a "moral school," the research bridges classical philology with modern character development needs. Consequently, classical Arabic texts serve as vital resources for nurturing empathy and servant leadership among Indonesian youth, effectively countering contemporary ethical crises through the timeless wisdom of the Islamic middle period's humanistic heritage and artistic depth.